Differential Interaction Strengths and Prey Preferences Across Larval Mosquito Ontogeny by a Cohabiting Predatory Midge. Issue 5 (30th April 2019) - Cuthbert, Ross N; Callaghan, Amanda; Dick, Jaimie T A
Abstract: Understandings of natural enemy efficacy are reliant on robust quantifications of interaction strengths under context-dependencies. For medically important mosquitoes, rapid growth during aquatic larval stages could impede natural enemy impacts through size refuge effects. The identification of biocontrol agents which are unimpeded by ontogenic size variability of prey is therefore vital. We use functional response and prey preference experiments to examine the interaction strengths and selectivity traits of larvae of the cohabiting predatory midge Chaoborus flavicans (Meigen 1830) (Diptera: Chaoboridae) towards larval stages of the Culex pipiens (Diptera: Culicidae) mosquito complex. Moreover, we examine the influence of search area variation on selectivity traits, given its importance in consumer-resource interactions. Chaoborids were able to capture and consume mosquito prey across their larval ontogeny. When prey types were available individually, a destabilizing Type II functional response was exhibited towards late instar mosquito prey, whereas a more stabilizing Type III functional response was displayed towards early instars. Accordingly, search efficiencies were lowest towards early instar prey, whereas, conversely, maximum feeding rates were highest towards this smaller prey type. However, when the prey types were present simultaneously, C. flavicans exhibited a significant positive preference for late instar prey, irrespective of water volume. Our results identify larval chaoborids as efficacious natural enemies of mosquito prey, with which they frequently coexist in aquatic environments. In particular, an ability to prey on mosquitoes across their larval stages, coupled with a preference for late instar prey, could enable high population-level offtake rates and negate compensatory reductions in intraspecific competition through size refuge.